Bioluminescent Vibrio fischeri Assays in the Assessment of Seasonal and Spatial Patterns in Toxicity of Contaminated River Sediments - Jarque, Sergio; Masner, Petr; Klánová, Jana; Prokeš, Roman; Bláha, Ludek (Frontiers in Microbiology, 2016)
Several bacteria-based assays, notably Vibrio fischeri luminescence assays, are often used as environmental monitoring tool for toxicity in sediments that may serve as both sinks and secondary source of contamination in aquatic ecosystems. In this study, we used 30-s kinetic bioassays based on V. fischeri to evaluate the toxicity associated to sediments from five localities with different contamination inputs (Morava River and its tributary Drevnice River in the south-eastern part of the Czech Republic). Toxicity assessed as half maximal inhibitory concentration (IC50) over the course of a year-long sampling was compared in bottom sediments and freshly trapped particulate material. Standard approach based on testing of aqueous elutriates was compared with toxicity of whole sediments (contact suspension toxicity). Bottom sediments showed lower toxicity compared to freshly trapped suspended materials in all cases. On the other hand, standardized elutriates induced generally weaker effects than suspended sediments likely due to losses during the extraction process. Toxicity generally increased during winter reaching maximum peaks in early spring months in all five sites. Total organic carbon (TOC) was found to be highly correlated with toxic effects. Toxicity from sites with direct industrial and agricultural water inputs also correlated with concentrations of metals, polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs). Single time point sampling followed by the extraction and testing of elutriates, do not truly reflect the spatial and temporal variability in natural sediments and may lead to underestimation of ecotoxic risks.